Bixafen, Prothioconazole, and Trifloxystrobin Alone or in Combination Have a Greater Effect on Health Related Gene Expression in Honey Bees from Nutritionally Deprived than from Protein Supplemented Colonies - Kato, Aline Y. [UNESP]; Freitas, Tainá A. L. [UNESP]; Gomes, Cássia R. A. [UNESP]; Alves, Thais R. R. [UNESP]; Ferraz, Yara M. M. [UNESP]; Trivellato, Matheus F. [UNESP]; De Jong, David; Biller, Jaqueline D. [UNESP]; Nicodemo, Daniel [UNESP] (MDPI, 2024)
The aim of this study was to evaluate whether alterations in food availability compromise the metabolic homeostasis of honey bees exposed to three fungicides alone or together. Ten honey bee colonies were used, with half receiving carbohydrate-protein supplementation for 15 weeks while another five colonies had their protein supply reduced with pollen traps. Subsequently, forager bees were collected and exposed by contact to 1 or 7 µg of bixafen, prothioconazole, or trifloxystrobin, either individually or in combination. After 48 h, bee abdomens without the intestine were used for the analysis of expression of antioxidant genes (SOD-1, CAT, and GPX-1), detoxification genes (GST-1 and CYP306A1), the storage protein gene vitellogenin, and immune system antimicrobial peptide genes (defensin-1, abaecin, hymenoptaecin, and apidaecin), through real-time PCR. All fungicide treatments induced changes in gene expression, with bixafen showing the most prominent upregulation. Exposure to 1 µg of each of the three pesticides resulted in upregulation of genes associated with detoxification and nutrition processes, and downregulation of immune system genes. When the three pesticides were combined at a dose of 7 µg each, there was a pronounced downregulation of all genes. Food availability in the colonies affected the impact of fungicides on the expression of the studied genes in forager bees.
Keywords: contact exposure; detoxification; fungicide; immunity; nutrition; RT-PCR